7 PENINGKATAN KREATIVITAS ANAK MELALUI ENTREPRENEURSHIP (Penelitian Tindakan pada Anak Kelompok B3 TK Insan Cemerlang Pringsewu Lampung Tahun 2015) - Asmira, Yulistyas Dwi (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT This research aims to improve children's creativity through entrepreneurship (market day). Using action research methods to model Kemmis & Taggart. The study was conducted from March to May 2015 and conducted over 13 meetings were divided into two cycles. Subjects in this study are the children of Kelompok B3 TK Insan Cemerlang Pringsewu, Lampung. The results showed an increase in children’s creativity after following the market day activities. The data show that the level of children’s creativity in pre-cycle is 46.58%. Children's creativity then increased to 64.5% at the end of the first cycle and increased again to 82.25% at the end of the second cycle. The results obtained based on observations during the study that the children play an active role in expressing his ideas, both when making decisions or when making crafts. Key words: Creativity, Entrepreneurship, Market Day, Action Research.